IMPLEMENTASI SISTEM DINAMIK PADA PENGEMBANGAN POLA KEMITRAAN INDUSTRI KECIL DAN MENENGAH DI DKI JAKARTA (Industrial and Systems Engineering Assessment Journal (INASEA), 2008)
Limited resources in developing small and middle industries in DKI Jakarta have made the growth of these industries to be slow. Small and middle industries must be subsidized by the government and investment companies. The industry itself is a complex system which consists of elements that are related each other so it produces a certain corporate character. Therefore, it is necessary to make a policy pattern of partnership between small and middle industry, government and investment companies. The approach in developing small and middle industries in DKI Jakarta is a system approach which is used System Dynamic tool. The system gives solution to the problem faced by industry by the following steps of problem identification, designing causal loop diagram, model development, simulation, test of sensitivity, and strategic efficiency analysis. The result yielded from the implementation of the dynamic system is to increase the development of small and middle industries in DKI Jakarta by using the pattern of partnership with government and investment companies.